Manipulation based on Fryette’s Laws increases heart rate variability and muscle flexibility in subjects with headache - Sakabe, Fabiana Forti; Sakabe, Daniel Iwai; Gonçalves, Gabriel Abreu; Santos, Paloma Bernardelli dos (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: The sympathetic nervous system has a direct connection with the cervical spine, through the cervical ganglia, in the superior cervical ganglion; therefore the manipulation of the superior cervical spine could result on modifications of the heart rate variability (HRV). Objective: To evaluate the immediate effect of the manipulation based on the Fryette’s laws of the superior cervical spinal (SCS) on HRV and posterior chain flexibility (PCF) in subjects with headache. Methods/Design: Twelve volunteers of both genders (23.8 ± 2.8 years), who had complaints of headache, participated in the study. Before and immediately after the HRV assessment, PCF was measured with the assistance of Wells and Dillon’s Bench test. For this the volunteer remained seated with the spine erect, lower limbs extended and feet resting on the bench. Then it was requested maximum flexion of the trunk and measured with a ruler the achieved distance. The HRV was obtained by the cardiofrequencymeter Polar RS800cx and captured for continuous fifteen minutes with the volunteer resting in supine position. At five minutes of collection, with the volunteer in the same position, the SCS manipulation technique (Fryette’s Laws) was performed bilaterally. The HRV assessment was performed in the time domain by the RMSSD index of RR intervals (Matlab For Windows version 6.1) in two different moments: before and after the manipulation. Statistical analysis consisted of the Kolmogorov-Smirnov test and paired t-test for comparison of pre and post manipulation variables (p<0.05). Results: There was a significant increase (p = 0.004) in the RMSSD index after the manipulation (from 42.58 ± 24.52 ms before the manipulation to 51.25 ± 27.55 ms ten minutes after manipulation). The PCF also increased significantly (p = 0.03) after the SCS manipulation (from 17.65 ± 11.9 cm to 21.40 ± 13.8 cm). Conclusions: The manipulation of SCS increased the HRV through the increase of the RMSSD index indicating a predominance of parasympathetic activity, and improved the PCF of the studied volunteers, also reduced signs and symptoms of headache.